UPAYA MENINGKATKAN KEMAMPUAN BELAJAR GAMBAR TEKNIK DENGAN METODE PROBLEM BASE LEARNING (PBL) SISWA KELAS XI JURUSAN AFP SMK PENERBANGAN AAG ADISUTJIPTO TAHUN PELAJARAN 2013/2014 - Andrieka Budi Sulistyiadi; Subagyo Subagyo (Jurnal Taman Vokasi, 2014)
Intention of Class Action Research (PTK)Â  to improving ability learn ability the student specially at subject draw the technique. This research executed in SMK Penerbangan AAG Adisutjipto year 2013 / 2014 .Research class ActionÂ  use Problem Base Learning method (PBL). Problem Base Learning Method (PBL) Research class Action is study process which starting points its study pursuant to internal issue real life, then from this problem is student stimulated to learn the problem pursuant to knowledge and experience which have been owned previously (prior knowledge) so that will be formed by a new experience and knowledge. this Research execution started from idea or literature, seenly is problem that happened the at school later; then determine the research step started from planning, action execution, perception and refleksiResult from this research indicate that the study process by using method of Problem of Base Learning method (PBL) Fox can be behavioral of student so that student more interested, more active and more accurate in course of study and earn increase of average value is overall of student posed at from value result of learning student which go up till 39,73%, interest 65,77%, livelines 55,92% and correctness 59,45Â